The perceptions of elite rink hockey head coaches: preparation/observation and intervention. - Sousa, T.; Sarmento, H.; Field, A.; Vaz, V. (International Journal of Performance Analysis in Sport, 2021)
The study explored the perception of rink-hockey head coaches in relation to the use of performance analysis as a tool to assist training and match preparation, observation and interventions. Seven experienced First Division Portuguese rink-hockey head coaches were included in the study. Semi-structured interviews were carried out and the data were analysed through inductive and deductive content analyses. Several themes emerged from the interviews including "preparation/observation" and "intervention". Rink-hockey head coaches prefer to analyse the opponents themselves to plan training, as well as to assist with tactical preparation and implement within-match strategies. They considered video analysis an important tool to analyse opponents` strengths and weaknesses, with particular focus on the opponent`s goalkeeper. Seek to identify qualities and deficiencies in the opponents` team and individual players. Focus the analysis of opponents` teams on the five moments of the game. Training intervention involves the adaption of training exercises, whereby information is communicated during meetings. These data have implications both from a performance and a training practice perspective. Future research should focus on players and goalkeepers` perspectives.